Motivational Value of Generation Z Toward Interior Elements of the Library and Archives Office Building in Pamekasan Regency - Achmad Fachriali Mulyadi; Susy Budi Astuti; Firman Hiwari (International Journal Labs, 2025)
The declining number of library visitors in Indonesia, particularly at the Pamekasan Regency Library and Archives Office, highlights the need for libraries to adapt to the preferences of Generation Z. This study explores the motivational values of Generation Z, based on Schwartz’s theory of 10 motivational values, and their relationship with library interior elements. The research aims to identify how libraries can redesign their spaces to align with the values of stimulation, benevolence, and achievement, thereby attracting more young visitors and enhancing their experience. Using a systematic literature review (SLR) method, the study analyzes relevant literature to understand the intersection between Generation Z’s values and library design. Findings reveal that Generation Z prioritizes innovation, flexibility, and technology-integrated spaces, favoring modern, multifunctional environments that support collaboration and productivity. Examples from the University of Indonesia Library and Surabaya’s Youth Center Public Library demonstrate successful implementations of such designs. The study recommends modular bookshelves, vibrant colors, optimal lighting, and digital infrastructure for the Pamekasan Library to create a more engaging and functional space. These changes can transform libraries into dynamic educational hubs, fostering creativity and increasing visitor numbers. The research underscores the importance of aligning library design with generational preferences to remain relevant in the digital era.